1996
DOI: 10.1007/bf01691966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an antigencapture enzyme immunoassay for detection ofEntamoeba histolytica in stool samples

Abstract: In order to identify the prevalence of Entamoeba histolytica in tourists with diarrhoea returning from countries of the developing world, sensitivity and specificity of a commercially available enzyme immunoassay (EIA) kit for the detection of Entamoeba histolytica coproantigen in stool were evaluated. Five hundred seventy-seven specimens from 469 patients were examined by microscopy and EIA. Sixty-two specimens from 49 patients were considered positive for Entamoeba histolytica. Compared with microscopic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…Jelinek et al reported that the sensitivity and specificity of the ProSpecT ELISA were 73.5 and 97.7%, respectively, compared to microscopy for E. histolytica/E. dispar in German travelers returning from vacation trips abroad (99).…”
Section: Antigen Detectionmentioning
confidence: 99%
“…Jelinek et al reported that the sensitivity and specificity of the ProSpecT ELISA were 73.5 and 97.7%, respectively, compared to microscopy for E. histolytica/E. dispar in German travelers returning from vacation trips abroad (99).…”
Section: Antigen Detectionmentioning
confidence: 99%
“…A monoclonal antibody-based ELISA for the specific detection of E. histolytica antigen in fecal samples (TechLab E. histolytica II ELISA; TechLab, Blacksburg, VA, USA) is commercially available; however, this test can neither detect E. dispar nor E. moshkovskii, and it is not useful for patients with invasive amebiasis [15,17,18]. The sensitivity of coproantigen ELISA is reported to be 60-100% [13,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that up to 90% of these patients are infected with the nonpathogenic species E. dispar and not E. histolytica (7,11,14,35). Because cysts of E. histolytica are morphologically similar to those of E. dispar, other techniques (e.g., PCR and ELISA for detection of specific antigens) are in use for differentiation of species from stools (8,32).…”
Section: Discussionmentioning
confidence: 99%